Distinct laccase expression and activity profiles of Trametes versicolor facilitate degradation of benzo[a]pyrene - Sun, Yueming; Li, Ying; Liang, Hong; Li, Ming; Liu, Ye; Wang, Litao; Lai, Weijian; Tang, Teng; Diao, Yongzhao; Bai, Yuhong; Jørgensen, Christian Isak; Xu, Wanghui; et al. (Frontiers in Bioengineering and Biotechnology, 2023)
A Trametes versicolor isolate from the Changbai Mountain showed promising activity in degrading benzo[a]pyrene (BaP), which is a high molecular weight (HMW) polycyclic aromatic hydrocarbon (PAH) compound. It was hypothesized that the T. versicolor isolate encode BaP-degrading enzymes, among which laccase is mostly sought after due to significant commercial potential. Genome of the T. versicolor isolate was sequenced and assembled, and seven laccase homologues were identified (TvLac1-7) as candidate genes potentially contributing to BaP degradation. In order to further identify the BaP responsive laccases, time-course transcriptomic and proteomic analyses were conducted in parallel on the T. versicolor isolate upon BaP treatment. Homologous laccases showed distinct expression patterns. Most strikingly, TvLac5 was rapidly induced in the secreted proteomes (secretomes), while TvLac2 was repressed. Recombinant laccase expression and biochemical characterization further showed corresponding enzymatic activity profiles, where TvLac5 was 21-fold more effective in BaP degradation compared to TvLac2. Moreover, TvLac5 also showed 3.6-fold higher BaP degrading activity compared to a commercial laccase product of T. versicolor origin. Therefore, TvLac5 was concluded to be a BaP-responsive enzyme from T. versicolor showing effective BaP degradation activity.